Differential effects of spinalization on discharge patterns and discharge rates of simultaneously recorded nociceptive and non-nociceptive spinal dorsal horn neurons - Sandkühler, Jürgen; Eblen-Zajjur, Antonio Alejandro; Fu, Q. -G.; Forster, C. (Pain, 1995)
Recordings were made simultaneously from 2-5 neurons at the same site in the lumbar spinal dorsal horn of pentobarbital-anesthetized rats. Neurons were classified as low-threshold (LT) or multireceptive (MR) according to their responses to non-noxious mechanical or noxious radiant heat stimuli of the skin. At the same recording sites neurons could be encountered which belong to different classes and/or which had mechanoreceptive fields which did not overlap. Cold blocks of the upper or lower thoracic cord or transsections of the upper cervical cord were made to evaluate the effects of spinalization on both the rate and pattern of background activity and/or noxious heat-evoked responses of different dorsal horn neurons under identical experimental conditions. At 24 of 27 recording sites, spinalization had qualitatively or quantitatively different effects on the rate of background activity of simultaneously recorded neurons. Interspike interval (ISI) means of background activity were significantly reduced in 29 of 65 (44.6%) neurons, prolonged in 23 of 65 (35.4%) neurons, or unchanged in 13 of 65 (20%) neurons. MR neurons displayed a significantly higher incidence of decreased background activity 17 of 45 (37.8%) and a lower incidence of increased background activity (18 of 45, 40%) during spinalization that the LT neurons from which 1 of 12 (8.3%) decreased and 8 of 12 (66.6%) increased background activity. Almost all (95.4%) neurons changed their discharge patterns after spinalization. At 9 of 27 recording sites, the discharge patterns of simultaneously recorded neurons were affected differently by spinalization as revealed by the coefficient of dispersion of the interspike intervals (ISI), indicating changes in the tendency to discharge action potential in clusters (bursts). At the same recording sites the level of noxious heat-evoked responses of simultaneously recorded MR neurons was also differentially affected by spinalization. Nociceptive responses were significantly enhanced in 19 of 37 (51.4%) neurons (137.8 ± 142.6%) of control, mean ± SD), reduced in 13 of 37 neurons (35.1%) (by 58.9 ± 20.9%) and/or unchanged in 5 of 37 (13.5%) neurons. It is concluded that no general ‘tone’ of descending antinociception exists and that tonic descending excitatory and inhibitory systems may be active simultaneously modulating both the level and pattern of neuronal discharges.
Online 5 April 2000
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 03.05.2021